2022
DOI: 10.1001/jamanetworkopen.2022.48453
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms in Individuals With Persistent Postconcussion Symptoms: A Systematic Review and Meta-Analysis

Abstract: ImportanceApproximately 15% to 30% of individuals with a history of concussion present with persistent postconcussion symptoms (PPCS). Individuals with PPCS are at greater risk of experiencing depressive symptoms.ObjectiveTo synthesize the association between depressive symptoms and PPCS in children, adolescents, and adults via meta-analysis and to investigate potential moderators of that association.Data SourcesSystematic search of Ovid Medline, CINAHL, PsycInfo, and Embase from 1995 to January 2022 was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Our model showed a strong correlation and significant, positive direct effect between concussion symptoms and depression status. This is consistent with the previously described 18-study systematic review of patients (N = 9101) with a history of concussion, which showed a large effect of concussion symptoms on depression status (Lambert et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our model showed a strong correlation and significant, positive direct effect between concussion symptoms and depression status. This is consistent with the previously described 18-study systematic review of patients (N = 9101) with a history of concussion, which showed a large effect of concussion symptoms on depression status (Lambert et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Identifying the precursors of depression in these patients, and the factors that may protect them against depression, may facilitate interventions that improve health outcomes (Juengst et al, 2017). Moreover, individuals displaying concussion symptoms often exhibit intense depressive symptoms (Ho et al, 2020), as supported by a meta-analysis of 18 studies involving 9101 participants (Lambert et al, 2022) and a scoping review of 25 studies (Sheldrake et al, 2022). Concussion symptoms following mild traumatic brain injury jeopardize both mood status, particularly depression, and sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Prominent in mood and anxiety disorders, these symptoms are typically transient in concussion, resolving within one to two weeks of injury [ 32 ]. However, in some adolescents, these symptoms persist for longer (more than four weeks), with a significant minority experiencing emotional dysregulation symptoms up to one year post-injury [ 17 , 18 , 37 , 38 ]. For example, in a large ( N = 14,765) sample of high school students in the United States, 36% of students with a concussion history reported persistent depressive symptoms for up to 12 months [ 35 ].…”
Section: Emotional Dysregulation Following Concussionmentioning
confidence: 99%
“…This may lead to persistent symptomatology, with approximately 21–35% of concussed adolescents developing PPCS [ 14 , 15 , 16 ]. PPCS in adolescents can adversely affect social functioning and academic performance [ 4 ] and are often associated with emotional dysregulation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an Ohio based study, 1 in 5 adults reported a TBI with loss of consciousness and for 10% of respondents the TBI occurred before they were 15 years old ( Corrigan et al, 2018 ). TBI are associated with long-term health issues including increased risk of stroke ( Esterov et al, 2023 ), early onset dementia ( Bellomo et al, 2022 ), depression ( Lambert et al, 2022 ), and decreased olfaction ( Tai et al, 2022 ). Post-TBI sequelae frequently include fatigue and altered cognition that compromise quality of life and productivity as described by the brain injury associated fatigue and altered cognition syndrome (BIAFAC) ( Yuen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%